Capitalism, The State and Social Work: Economic Transformations and Global Challenges - García, Rubén Gregorio Pérez; Félez, José Luis Anta; Miranda, María del Carmen Sánchez (Journal of Posthumanism, 2026)
We analyse the evolution of capitalism from the Industrial Revolution to the present day, highlighting the relationship between capital, the state and the global economy, and its influence on social work. We review the cycles of growth and crisis linked to technological innovation and market expansion, pointing out their effects on structural inequality and job insecurity. Throughout the 20th century, globalisation and the power of large corporations limited the capacity of the state and conditioned social policies. Within this framework, social work managed the consequences of capitalist crises, oscillating between welfare and the defence of rights, in tension with the commodification of public services. With digitalisation, precariousness is intensifying, redefining professional interventions. We propose the challenge for social work to adopt a critical stance towards the economic dynamics that reproduce inequality and to explore transformative strategies based on social justice.